1984
DOI: 10.1002/j.1460-2075.1984.tb02026.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and selection in the generation of class II histocompatibility antigen polymorphism.

Abstract: A comparison of seven human DR and DC class II histocompatibility antigen beta‐chain amino acid sequences indicates that the allelic variation is of comparable magnitude within the DR and DC beta‐chain genes. Silent and replacement nucleotide substitutions in six DR and DC beta‐chain sequences, as well as in seven murine class II sequences (three I‐A beta and four I‐A alpha alleles) were analyzed. The results suggest that the mutation rates are of a comparable magnitude in the nucleotide sequences encoding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(75 citation statements)
references
References 47 publications
4
71
0
Order By: Relevance
“…4 and Table 1). Furthermore, as has been observed previously (26), the majority of nucleotide differences outside the first domain are silent, presumably reflecting structural and functional constraints, while the majority of nucleotide differences within the first domain result in amino acid differences. It should also be noted that many of the amino acid differences are clustered within an area (positions 45-56) previously suggested to be "hypervariable" (38).…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…4 and Table 1). Furthermore, as has been observed previously (26), the majority of nucleotide differences outside the first domain are silent, presumably reflecting structural and functional constraints, while the majority of nucleotide differences within the first domain result in amino acid differences. It should also be noted that many of the amino acid differences are clustered within an area (positions 45-56) previously suggested to be "hypervariable" (38).…”
Section: Methodssupporting
confidence: 67%
“…No recombinational event between DQ and DR has yet been confirmed, suggesting a relatively low frequency of recombination. Biochemical studies (2,(12)(13)(14)(15)(16)(17)(18) and analysis of cDNA clones (19)(20)(21)(22)(23)(24)(25)(26) indicate that a majority of the Ia genes are expressed as products. Ia gene products belonging to the same group are highly related (greater than 95% protein homology) while those belonging to different groups are only approximately 60% related.…”
Section: Introductionmentioning
confidence: 99%
“…It has been speculated that this degree of diversity is a correlate of the biological functions of the molecules encoded in the MHC region. The extensive population polymorphism of the MHC genes may have resulted from selective pressures and functional adaptations [8][9][10]. It has been shown that the highest degree of variability of MHC proteins is found in residues pointing toward the peptide-binding region [11,12].…”
Section: Genetic and Functional Variation Of Major Histocompatibilitymentioning
confidence: 99%
“…Recombinant plasmid DNA was isolated from seven clones and sequenced by the dideoxy chain termination method in both directions. To ensure specific amplification of platelet's RNA, RT-PCR reactions were performed using a set of oligonucleotide primers for the non-polymorphic domain of the beta chain gene of class II HLA-DR molecule (which is found predominantly on the surface of activated T-cells, B-cells, and antigen-presenting cells) [19] and in a different reaction, the same platelet's RNA was used in RT-PCR with synthetic oligonucleotides based on the sequence of the platelet membrane glycoprotein lib (GPIIb) [20] as described by Gardella et al [21]. PCR amplification using oligonucleotides 03F and 03R, was performed for 25 cycles of 30 s at 94°C, 30 s at 52°C, and 40 s at 72°C.…”
Section: Pcr Amplification and Dna Sequencingmentioning
confidence: 99%